Interview with William Carroll. The Basic Issues of Capitalism in the XIX Century are Still Vital in the XXI Century (translated by Elena Konobeeva) - CarrollWilliam K. (Journal of Economic Sociology, 2013)
William Carroll, Professor of Sociology at University of Victoria, wasinterviewed during the conference “Embeddedness and Beyond: Do Sociological Theories meet Economic Realities?” in Moscow (October 25–28, 2012), where Carroll chaired a section of mini-conference “Capitalist Globalization and Its Alternatives” and at the same time presented his research project entitled “Embedding Postcapitalist Alternatives: The Global Network of Alternative Knowledge Production and Mobilization”. In his interview Carroll disserts upon postcapitalism as a possible way for moving away from class society towards economic democracy, as well as upon opportunities and consequences of that move; moreover, capitalist mode of production, income polarization and current environmental problems are criticized in reference to global world. According to Carroll today’s capitalist society is not democratic in its full meaning, because democracy represents a kind of autocracy that is market mediated, and society is differentiated by its income in proportion 1 : 99%. The second important question of capitalism is ecology issue, implying that capitalist mode of production necessarily requires endless grow, while our resources are limited. At the same time, the problems of capitalism dated by the XIX century are still of immediate interest.